Pemberian Ekstrak Daun Kemuning (Murraya paniculata (L.) Jack) dalam Air Minum terhadap Performa dan Kualitas Fisik Telur Puyuh Malon: The Effect of Additional Supplementation of Kemuning (Murraya paniculata (L.) Jack) Leaves Extract into Drinking Water on Performance of Malon Quail Eggs (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
The aim of this study was to determine the effect of kemuning leaves (Murraya paniculata (L.) Jack) extract supplementation of the drinking water on performance and physical quality of egg. Twenty-four weeks old of malon hybrid quails which amounts to 240 birds were allocated in a Completely Randomized Design with four treatments and two replications.  The treatments were namely P0 = control (without kemuning leaves extrct), and added kemuning leaves extract into drinking water (4 consecutive days per weeks) with dose of 3% (P1),  5%  (P2) and 7%  (P3). The commercial diet used in this study contained 20.01 % of crude protein. The results showed that supplementation of 3% and 7% of kemuning leaves extract into drinking water  had no significant difference on performance and physical quality  of egg. It was concluded that the dose of 5% kemuning leaf extract addition into total drinking water tends to produce the highest egg production (85%).Key words:          Murraya paniculata (L.) Jack, performance malon quail, egg physical quality DAFTAR PUSTAKAAndari, A, Anisa EN, Wulandari RF & Suci DM. 2018.  Efek suplementasi jamu rempah pada puyuh (Coturnix coturnix japonica) terhadap performa dan kadar kolesterol telur.  Jurnal Ilmu Nutrisi dan Teknologi Pakan 16 (2): 34-41Adfa, M.2007.  Isolasi senyawa flavonoid aktif berkhasiat sitotoksik dari daun kemuning (Murraya paniculata L.Jack).  Jurnal Gradien 3(2): 262-266Halimah, H, Suci, DM &Wijayanti I.2019.  Studi potensi penggunaan daun mengkudu (Morinda citrifolia L.) sebagi bahan antibakteri Escherichia coli dan Salmonella typhimurium. Jurnal Ilmu Pertanian Indonesia 24 (1): 56-64Hanusova E,  Hrnčár C, Hanus A, & Oravcová M. 2016.  Egg traits in Japanese quail.   Acta Fytotechnica et Zootechnica 19 (Special Issue) : 62-67Hilmi,M, Sumiati & Astuti DA. 2015.  Egg production and physical quality in Coturnix-coturnix Japonica fed diet containing piperine as phytogenic feed additive. Media Peternakan 38 (3): 150-155Hrnčár C,  Hanusová E,  Hanus A & Bujko J. 2014.  Effect of genotype on egg quality characteristic of Japanese quail (Coturnix Japonica).  Slovak Journal of Animal Science 47(1): 6-11.Iskender H, Yenice G, Dokumacioglu E, Kaynar O, Hayirli A, & Kaya A. 2016.  The effect of dietary flavonoid supplementation on the antioxidant status of laying hens.  Brazilian Journal of Poultry Science. 18 (4): 663-668Nowaczewski S, Kontecka H, Rosiñski A, & Koronowsk SBP. 2010.  Egg quality of Japanese quail depends on layer age and storage time. Folia biologica (Kraków) 58(3-4): 201-207Nugroho, AE, Riyanto S, Sukari MA, Maeyama K. 2010.  Efek senyawa flavonoid dari kemuning (Murraya paniculata [L.] Jack terhadap pelepasan histamin dari kultur sel mast. Majalah Obat Tradisional 15 (1): 34-40Parubak A S, 2013.  Senyawa flavonoid yang bersifat antibakteri dari Akway (Drimys becariana Gibbs). Chemistry Progress 6 (1): 34-37Prajonggo TS, DjatmikoW & Soemarno. 1983. Pengaruh Sauropus androgynus L. Merr terhadap gambaran hisotologi kelenjar susu mencit betina yang menyusui. Prosiding Kongres Nasional XI FSI. Jakarta (ID): Hlm 735-739.Saerang LP, Josephine, Yuwanta T & Nasroedin. 2000. Pengaruh minyak nabati dan lemak hewani dalam ransum puyuh petelur terhadap performa daya tetas, kadar kolesterol dan plasma darah. Buletin Peternakan 22(2):96-101Setyaningrum S & Siregar DJS. 2015. Efektivitas minuman herbal terhadap pertumbuhan puyuh. Surya Agritama.  4:1:109-117Siregar B. 2008. Pengaruh penambahan tepung daun singkong (Manihot utilisima crantz) dalam pakan terhadap performans produksi telur puyuh (Cortunix-cortunix japonica) petelur. Jurnal Ilmiah Ilmu-Ilmu Peternakan 11(1):28-33.Song KT, Choi SH, & Oh HR. 2000. A comparison og egg quality of pheasant, chukar, quail, and guinea fowl. Asian Australasian Journal Animal Science 13 (70): 986-990Stojčić MD, Milošević N,  Perić L,  Jajić I, & Tolimir N.  2012.  Egg Quality of Japanese quail in Serbia.  Biotechnology in Animal Husbandry 28(3): 425-431Subekti, S. 2007. Senyawa fitosterol dalam daun katuk (Sauropus androgynous L. Merr) dan pengaruhnya pada fungsi reproduksi puyuh. [disertasi]. Sekolah Pascasarjana: Institut Pertanian BogorSultana F, Islam MS & Howlider MAR. 2007.  Effect of dietary Calcium sources and levels on egg production and egg shell quality of Japanese quail. International Journal of Poultry Science 6 (2): 131-136Zainuddin D & Wibawan IWT. 2007. Biosekuriti dan Manajemen Penanganan Penyakit Ayam Lokal. Dwiyanto K, Prijono ST, editor. Bogor (ID): Pusat Penelitian Biologi LIPI.Zita L, Ledvinka Z & Klesalova L. 2013.  The effect of the age of Japanese quails on certain egg quality traits and their relationships. Veterinarski Archive 83 (2) : 223-232.Yilmaz, A, Tepeli C & Çağlayan T. 2011.  External and internal quality characteristics in Japanese quails of different plumage color lines. Journal of Food Agriculture and Environment 9 (2): 375-379Yuhernita & Juniarti. 2011. Analisis senyawa metabolit sekunder dari ekstrak methanol daun Surian yang berpotensi sebagai antioksidan.  Makara Sains 15(1): 48-52